STUDY OF ADVERSE DRUG REACTIONS TO ATYPICAL ANTIPSYCHOTIC DRUGS IN PSYCHIATRIC ILLNESS - DR.VERMA HEMLATA,; DR.VERMA VK,; DR. RAO SS, (International Journal of Pharma and Bio Sciences, 2014)
Atypical antipsychotics are commonly used drugs for mental disorders, so early detection of ADRs in patients treated with antipsychotics becomes necessary. This study is a longitudinal prospective observational study of ADRs of Atypical Antipsychotic drugs in patients of psychiatric illness. Information of ADRs was data based and collected from OPD. The noted ADRs were assessed by using Naranjo’s probability assessment scale, and WHO (UMC) causality assessment scale. We recorded 104 ADRs due to atypical antipsychotics. Majority of patients in this study belonged to 21-30 years age group which was 24% of the total. According to the severity of ADRs, majority of cases were reported of having weight gain 38.46% followed by sedation 19.23%, dry mouth 13.46% and orthostatic hypotension 5.76% . 88.47% were reported as type A and 11.53% were reported as type B. Definite (certain) relationship was established in 30.40% patients while probable in 57.62% and 11.53% ADRs were categorized as possible. The ADRs can be prevented by collecting reliable information about their frequencies and possible risk factors.